Potential ecological hazard of pure metals - Levenets, V.V.; Rolik, I.L. (Вопросы атомной науки и техники, 2020)
The potential environmental hazard of a number of pure metals was assessed. A comparative analysis of hazard indicators established by various international organizations (WHO, ACGIH, etc.) and hazard factors regulated by the Globally Harmonized System of Classification and Labeling of Chemicals was conducted. The assessment was carried out for the following metals: aluminum, beryllium, vanadium, cadmium, manganese, arsenic, nickel, lead, titanium, zinc, zirconium.